The effects of long term strength training on hemodynamic parameters and resistin level in postmenopausal women - Marin, Cecília Tardivo (2014)
Objective: Investigate the influence of strength training (ST) on serum resistin levels and blood pressure of postmenopausal women. Methods: Longitudinal study conducted at the Federal University of São Carlos with twenty-three sedentary postmenopausal women. The ST lasted 13 months (Dec./2008 to Jan./2010) and consisted of two weekly sessions with three sets of 8-12 maximum repetitions and one exercise for each main muscle group. Maximum muscular strength was tested in the following exercises: bench press, 45° leg press, and standing arm curl. Serum resistin level was determined using the ELISA method. ANOVA (with repeated measures) was used for the comparisons between periods Pre-, 6 months and 13 months (p < 0.05); Pearson’s correlation test was used to evaluate the correlations between resistin × blood pressure, resistin × muscle strength and strength × blood pressure. Results: Women presented the following anthropometric profile: 61.33±3.8 years; height 148.5±32.7 cm; body mass 67.56±10.85 kg. The ST decreased resistin levels (30272.4 ± 8100.1 to 16350.6 ± 2404.6 pg/mL) and systolic blood pressure (120.5 ± 11.8 to 115.8 ± 1.6 mmHg), and increased muscular strength in the leg press 45o (172.3 ± 27.3 to 348.6 ± 40.8kg), bench press (31.9 ± 4.1 to 41.8 ± 5.6 kg) and arm curl (21.0 ± 2.4 to 26.5 ± 2.9 kg) after 13 months (p < 0.05). Conclusion: The results of this study revealed that long-term ST increases maximum muscular strength, decreases systolic blood pressure and serum resistin levels, which are beneficial physiological alterations that reduce the risk for cardiovascular diseases in postmenopausal women. doi:10.5020/18061230.2013.p325